Analysis of Sharia Financial Literacy and Trust in Increasing Interest in Digital Sharia Banking Services - Kartina Kartina; Mukhlishin Mukhlishin; Nur Fitri Hidayanti (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effect of Islamic financial literacy and trust on individuals’ intention to use digital Islamic banking services in Indonesia, given the inconsistencies found in previous empirical studies regarding the roles of these two variables. This research employs a quantitative approach with a survey design, involving 114 respondents who are users and potential users of digital Islamic banking services, selected using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of JASP software. The results indicate that both Islamic financial literacy and trust have a positive and significant effect on the intention to use digital Islamic banking services, both partially and simultaneously, with a significance level of p < 0.001. These findings provide empirical evidence that improving individuals’ understanding of Islamic financial principles, accompanied by strengthening trust in banking systems and institutions, plays a crucial role in encouraging the adoption of digital Islamic banking services, particularly among younger generations. The practical implications of this study highlight the importance of developing digital Islamic banking strategies that integrate Islamic financial literacy education, information transparency, and the enhancement of system security and reliability in order to increase public trust and participation.